До встречи с тобой: [роман] / Джоджо Мойес - Мойес Джоджо (Иностранка, 2015)
Экземпляры: аб. (20150330) / Инвентарный номер: 51508 / Цена: 326. 00. / Сис.шифр: И(4 Вел) / Авт.знак: М 74 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44